Cutaneous metastasis of signet ring cell appendiceal adenocarcinoma: a herald of disease recurrence - Seyffert, Jennifer L.; Bibliowicz, Nathan; Wong, Christopher; Wangia, Michael (International Journal of Research in Dermatology, 2020)
Signet ring cell appendiceal adenocarcinoma (SRCAA) is a rare entity with poor prognosis and high tendency for metastasis to pelvic lymph nodes, ovaries, and peritoneal surfaces. Despite numerous reports of intra-abdominal metastasis, there have been few reported cases of cutaneous SRCAA metastasis. We report a rare case of SRCAA metastatic to the cutaneous abdominal wall in a 67 years old female, which was first presenting sign of disease recurrence.